Barriers to access and the purchasing function of health equity funds: lessons from Cambodia - Maryam Bigdeli; Peter Leslie Annear (The World Health Organization, 2009)
PROBLEM: High out-of-pocket payments and user fees with unfunded exemptions limit access to health services for the poor. Health equity funds (HEF) emerged in Cambodia as a strategic purchasing mechanism used to fund exemptions and reduce the burden of health-care costs on people on very low incomes. Their impact on access to health services must be carefully examined. APPROACH: Evidence from the field is examined to define barriers to access, analyse the role played by HEF and identify how HEF address these barriers. LOCAL SETTING: Two-thirds of total health expenditure consists of patients' out-of-pocket spending at the time of care, mainly for self-medication and private services. While the private sector attracts most out-of-pocket spending, user fees remain a barrier to access to public services for people on very low incomes. RELEVANT CHANGES: HEF brought new patients to public facilities, satisfying some unmet health-care needs. There was no perceived stigma for HEF patients but many of them still had to borrow money to access health care. LESSONS LEARNED: HEF are a purchasing mechanism in the Cambodian health-care system. They exercise four essential roles: financing, community support, quality assurance and policy dialogue. These roles respond to the main barriers to access to health services. The impact is greatest where a third-party arrangement is in place. A strong and supportive policy environment is needed for the HEF to exercise their active purchasing role fully.